1997
DOI: 10.1046/j.1365-2516.1997.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations in 28 Italian and Iranian patients with severe factor VII deficiency

Abstract: There has been wide variation in the reported haemorrhagic manifestations of factor VII deficiency. We examined type and frequency of clinical manifestations in 28 Iranian and Italian patients with severe deficiency (factor VII coagulant activity 2% or less). The most frequent symptoms were epistaxis and menorrhagia, whereas soft tissue bleeding such as haemarthrosis and muscle haematoma was less frequent. Only 5 of 9 patient who underwent surgery without factor VII replacement therapy had postoperative bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 10 publications
4
82
1
1
Order By: Relevance
“…Some local studies of RBDs showed that FVII, FXIII and FX deficiencies are similar to what has been observed in our neighboring countries like India and Iran [13,14]. However in India, there is regional variation.…”
Section: Discussionsupporting
confidence: 74%
“…Some local studies of RBDs showed that FVII, FXIII and FX deficiencies are similar to what has been observed in our neighboring countries like India and Iran [13,14]. However in India, there is regional variation.…”
Section: Discussionsupporting
confidence: 74%
“…Intermediate values around 30-40% of normal were obtained using human placenta or human recombinant thromboplastin (h-thromboplastin) was used [158]. Those findings have been confirmed by other studies [159,160,161].…”
Section: Measurement Of Fvii By Using Different Thromboplastinssupporting
confidence: 58%
“…FVII deficiency previously, considered extremely rare, is now considered to be the most common autosomal recessive clotting factor deficiency, with a prevalence of 0.5-1.0 per 10 6 in some populations [5], such Italian and Iranian. There have been no published reports of the prevalence of severe factor VII deficiency in the African-American population.…”
Section: Discussionmentioning
confidence: 99%